Why the Extractive Industry Should Support Mandatory Transparency:3 A Shared Value Approach. (3rd September 2013) - Topal, Julien; Toledano, Perrine
Abstract: The Transparency Amendment, included in the Dodd‐Frank Wall Street Reform and Consumer Protection Act, can be an important tool in curtailing the resource curse that so heavily burdens resource‐rich developing countries by shedding light on opaque payments between the extractive sector and host countries. From the get‐go, however, extractive industry companies have fiercely opposed the new mandatory disclosure requirements as set out in this regulation. The corporate opposition is for the largest part motivated by the fear of a competitive disadvantage that derives from the fact that the amendment is housed with the Securities and Exchange Commission (SEC) and thus only holds jurisdiction over those that report to the SEC. Although on the one hand watering down these corporate fears, this article draws on the "shared value approach" and empirical evidence to argue that there is a business case for transparency. This refreshing take on transparency regulation invites corporate leaders to reassess their current oppositional stance and to embrace new initiatives like the Transparency Amendment and to take a proactive stance in building a convincing global regulatory system of transparency.